2016
DOI: 10.1155/2016/2860346
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Sex-Seeking Behavior Promotes HIV Infection Risk: A 6-Year Serial Cross-Sectional Survey to MSM in Shenyang, China

Abstract: HIV prevalence is still rapidly increasing among Chinese men who have sex with men (MSM). The Internet also makes it easier for MSM to have casual partners. This study aims to evaluate the trend of Internet-based sex-seeking behavior of MSM and its impact on HIV prevalence, the distribution of HIV subtype strains, and transmitted drug resistance rates. A serial cross-sectional study was conducted from 2009 to 2014. Of the 1,981 MSM, 50.5% (1,000/1,981) mainly sought homosexual partners through the Internet (In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 29 publications
2
20
1
1
Order By: Relevance
“…Participants in this study reported more sexual risk behaviors than in comparable Web-based samples of MSM in China, including more multiple sexual partnerships, infrequent or incorrect condom use, more frequent receptive anal sex, and less awareness of sexual partners’ HIV status [6,21]. The overall HIV prevalence (98/683, 14.3%) was also far higher than in a similar sample (24/341, 7.0%) [21].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Participants in this study reported more sexual risk behaviors than in comparable Web-based samples of MSM in China, including more multiple sexual partnerships, infrequent or incorrect condom use, more frequent receptive anal sex, and less awareness of sexual partners’ HIV status [6,21]. The overall HIV prevalence (98/683, 14.3%) was also far higher than in a similar sample (24/341, 7.0%) [21].…”
Section: Discussionmentioning
confidence: 79%
“…Facility-based HIV testing is defined as HIV testing conducted in health care facilities, including the Centers for Disease Control and Prevention (CDC), hospitals and clinics, and community-based organizations (CBOs) that conduct HIV antibody screening (often using rapid tests) with linkage services to health care facilities for those who screen positive. The public health utility of internet-based interventions is of growing interest in China owing to the expansion of internet access—internet and mobile internet users currently exceed 800 million people [5]—and the growing use of social networking apps for socializing and sexual partner seeking [6-9]. To date, internet-based interventions have been used to promote HIV testing in young MSM, promote HIV/hepatitis C virus testing among people who inject drugs, reduce HIV transmission among male sex workers, reduce pretreatment loss to follow-up in HIV-diagnosed individuals, and improve the adherence of antiretroviral therapy in people living with HIV/AIDS [10-14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that IPV victims seemed more likely to find their sexual partners over the internet. MSM who were recruited via the internet are more likely to encourage high-risk sexual behaviors 44 – 46 . These risky behaviors could increase the risk of acquiring HIV among IPV victims.…”
Section: Discussionmentioning
confidence: 99%
“…Men who have sex with men (MSM) are disproportionately affected by HIV [1-3]. The percentage of MSM with HIV and AIDS in China increased from 13.7% in 2011 to 28.3% in 2015 [4,5]. Understanding the driving forces of this epidemic is essential to provide tailored interventions to MSM.…”
Section: Introductionmentioning
confidence: 99%